The Utilization of Sago Frond Cellulose for Production of Prebiotic Hydrolyzate Through Enzymatic Hydrolysis - Ilham Marvie; Titi Candra Sunarti (Journal of Science, Technology, and Visual Culture, 2021)
Sago palm frond is the upper part of the sago palm trunk and is not utilized during sago harvesting. Sago palm frond contains low non-cellulose components; thus, it is the potential to be used as the production of cellulose hydrolysate. The result contains cello-oligosaccharides and cellobiose which can be utilized as a prebiotic that is beneficial to the human digestion system. The cellulolytic enzyme is used as a catalyst to produce intermediate hydrolysate. therefore, it requires a certain hydrolysis process. This research investigated the characteristics of sago palm frond and the extraction of its cellulose, and its application as a substrate for cellulose hydrolysis. The results showed that the upper half frond contains a higher crude fiber (35% wet basis) and cellulose components (37% wet basis) than the bottom one. Up to 72 hours the hydrolysis produced cello-oligosaccharides and cellobiose with a degree of polymerization of 7.9 and a dextrose equivalent of 12.6.